Penerapan Metode Snowball Throwing dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam Siswa Kelas III di SD Negeri Demakan 02 Tahun Ajaran 2021/2022 - Khusnul Fadlilah; Mukhlis Faturrohman; Iffah Mukhlisah (MODELING: Jurnal Program Studi PGMI, 2022)
This thesis discusses the use of the Snowball Throwing learning method to improve student learning outcomes in the subjects of Islamic Religious Education at the SD Negeri Demakan 02. With the background of the problem that the value of Islamic Religious Education in students is still below the standard and does not meet the KKM, so this research was conducted with the aim of improving the learning outcomes of Islamic Religious Education for grade III students of SD Negeri Demakan 02. This research is a collaborative type of classroom action research (CAR), which is analyzed descriptively and qualitatively. In collecting data, the methods of observation, tests, and documentation were used. The observation method is used to measure the activities of teachers and per cycle. The test method is used to determine students' learning abilities after participating in learning using the Snowball Throwing learning method. And the documentation method is used to describe what happened in the classroom during the learning process. The results of this study indicate that the use of the Snowball Throwing learning method is able to improve learning outcomes of Islamic Religious Education for class III students of SD Negeri Demakan 02, namely 37% in the first cycle and 85% in the second cycle. Based on the results of the analysis of the data obtained, it can be concluded that learning Islamic Religious Education using the Snowball Throwing learning method can improve student learning outcomes on the material prayer and remembrance after prayer from increasing test scores in each cycle.